Three-dimensional finite element analysis of shaping curved root canals with the ProTaper and HeroShaper systems - MUTLU MİTİL, BİLÇEN; EKİCİ, BÜLENT; ATAKÖK, GÜRCAN; KURT, MUSTAFA (SPRINGER HEIDELBERG, 2015)
In this study, we simulated the shaping of a curved root canal with the ProTaper and HeroShaper file systems using three-dimensional finite element modeling. A total of seven of the Ni-Ti rotary instruments were employed to investigate the influence of cutting geometry. A workflow was developed using the mechanical design and analysis software I-DEAS 11 and the LS-DYNA finite element package. The three-dimensional tooth model was constructed from a micro-computed tomography dental scan and a simulated canal. It was found that stresses concentrated towards the outer aspect of curvature in the apical portion of the canal when the ProTaper file system was employed. For the HeroShaper files, the stresses concentrated in the middle portion of the tooth model. Our simulated root canal procedure enables the efficacy of rotary NiTi instruments to be evaluated in a patient-specific setting. This may aid the dentist in choosing the optimal tool set and provides data for improving tool design.
Keywords: Root canal; Finite element analysis; HeroShaper; ProTaper